Body Composition, Physical Fitness, Physical Activity and Nutrition in Polish and Spanish Male Students of Sports Sciences: Differences and Correlations - López-Sánchez, Guillermo F. (Int J Environ Res Public Health, 2019)
It is important to study differences in body composition, physical fitness and lifestyle behaviours between university students from different countries to develop country-specific recommendations on health promotion to provide to students when transitioning to university. The present study aimed to analyse differences in body composition, physical fitness and lifestyle behaviours between Polish and Spanish students of Sports Sciences. One-hundred-and-eighty-six male students participated (81 from Poland and 105 from Spain). Polish males were on average 21.5 ± 1.9 yrs old and Spanish males 21.5 ± 2.5. The body composition variables measured were body weight (kg), fat-free mass (FFM, kg and %), fat mass (FM, kg and %), total body water (TBW, kg and %), basal metabolic rate (BMR, kcal), body mass index (BMI, kg/m(2)), fat-free mass index (FFMI, kg/m(2)) and fat mass index (FMI, kg/m(2)). The physical fitness variables measured were squat jump (SJ, height in cm, power in watts and w/kg), countermovement jump (CMJ, height in cm, power in watts and w/kg), running speed (10, 20 and 30 m (time in s)), and progressive aerobic cardiovascular endurance run (PACER, stage, final speed in km/h, distance in m, VO(2)max in mL/kg/min). Lifestyle variables measured were vigorous physical activity (VPA, days/week, min/week), moderate physical activity (MPA, days/week, min/week), walking (days/week, min/week), sitting (min/week), meals/day, vegetables/day, fruits/day, seafood/week, dairy products/week, sweets, chips, fast food/week, litres of liquid/day, litres of sugary drinks/day, alcohol/week and cigarettes/day. In comparison to Spanish students, Polish students had greater FFM (kg), greater TBW (kg), higher BMR, greater power in SJ, greater height and power in CMJ, lower times in running speed tests (10 and 20 m) and greater consumption of vegetables and liquids. In comparison to Polish students, Spanish students participated in more physical activity, and consumed more seafood, more dairy products, less sugary drinks, less alcohol and less tobacco. VPA and consumption of vegetables and liquids had positive influences on body composition and physical fitness. According to these results, universities should promote a healthy lifestyle in order to improve body composition and physical fitness in male students studying sport science. In the cases of Spain and Poland, special attention should be paid to the weak points detected in this study. This would be useful for avoiding future risk of diseases such as obesity or diabetes.